2021
DOI: 10.1182/blood.2020005112
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of extranodal stage I diffuse large B-cell lymphoma in the rituximab era

Abstract: This retrospective study aimed to better define the characteristics and outcomes of extranodal stage I DLBCL in the rituximab era. Patients diagnosed with stage I DLBCL from 2001-2015 treated with rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone (R-CHOP) or R-CHOP-like regimens with or without radiation (RT) were included. We identified 1955 patients with newly diagnosed DLBCL, of whom 341 had stage I and were eligible for this analysis. Extranodal presentation was observed in 224 (66%) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
1
34
2
1
Order By: Relevance
“…Our study observed that, among 289 patients, the 4-year PFS and OS rates were 90.3 and 94.1%, respectively, much higher than those in patients receiving chemotherapy alone (24). Besides that, extranodal involvement showed no obvious influence on either PFS or OS in localized DLBCL, which seems contradictory with a previous report that addressed the inferior survival of extranodal disease (9). This may be attributed to the different study enrollments between two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study observed that, among 289 patients, the 4-year PFS and OS rates were 90.3 and 94.1%, respectively, much higher than those in patients receiving chemotherapy alone (24). Besides that, extranodal involvement showed no obvious influence on either PFS or OS in localized DLBCL, which seems contradictory with a previous report that addressed the inferior survival of extranodal disease (9). This may be attributed to the different study enrollments between two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be attributed to the different study enrollments between two studies. Moreover, compared with the previous study ( 9 ), our study included more SE patients with GI tract involvement that was related to favorable outcomes but less SE patients with bone involvement that was related to unfavorable outcomes ( 17 ). As reported in DLBCL ( 25 ), serum LDH was also recognized as an unfavorable prognostic factor in localized DLBCL, indicating that more potentially effective immunochemotherapy regimen should be applied in this subset of localized DLBCL patients to improve their outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was mostly observed in patients with advanced disease [8,10,28]. More recent studies suggest that radiotherapy might be omitted in PET-negative patients [41,42]. It is noteworthy that it was difficult to precisely analyze the impact of radiotherapy in our cohort, as some patients received radiotherapy early during treatment and some as consolidation therapy.…”
Section: Discussionmentioning
confidence: 93%
“…By analyzing tumor reservoirs persisting after treatment, they also show that clonal selection-induced resistance results from a different mechanism in HR patients. 1 In MM, patients displaying HR cytogenetic features have similar levels of complete response as standard-risk (SR) patients, but shorter progression-free survival (PFS) and overall survival (OS), which is why response duration is more important than the depth of response. 2 However, thanks to the recent MRD revolution, it is possible to evaluate the response to treatment with unprecedented sensitivity; consequently, it is possible to better identify patients who will progress soon among those in a conventional complete response.…”
Section: Undetectable Mrd Can Change the Dealmentioning
confidence: 99%